Environmental costs management in enterprises of chemical industry - Hyršlová, Jaroslava (Univerzita Pardubice, 2000)
At present, it is necessary to trace, track and evaluate environmental costs of enterprises. Today's environmental compliance costs are huge and stll increasing for many enterprises, and the costs of the information systems tracing environmentally related costs are lelatively small compared to those of not tracing. Tracing, tracking and evaluating of environmental costs have gained importance for the correct calculation of the profitability of products, production sites and enterprises. The knowledge of environmental costs and their transparency represent the basis for taking environmentally relevant facts into consideration in decision making. the article summarizes the results of the research that was carried out in enterprises of chemical industry in the period of 1996 - 1999.
Keywords: environmentální management; podniky; chemický průmysl